TEAM WORK IN LANGUAGE EDUCATIONAL SPACE: FOREIGN EXPEIENCE - Ivanov, Yevhen; Kokarieva, Anzhelika (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
An important task in the modern educational environment is to determine the main directions of creating teams, research ways of their organization in modern conditions, ensure their successful functioning, evaluate the results obtained and provide team members with such significant knowledge, skills and abilities that would be flexible and applicable in various situations of life. The main goal of this study is to highlight the key aspects of understanding the essence of the team, to determine the main directions of its creation and functioning based on the analysis of the work experience of similar teams in the international educational environment. A number of general scientific methods were used in the research process: analysis (comparative analysis, content analysis), synthesis, classification, comparison, etc. Based on the analysis of the foreign experience of using team activities in the foreign language educational space, as a result, the peculiarities of building teams, their functioning, defining the tasks to be performed, as well as the types of teams that exist in the foreign language educational space were revealed. Special attention was paid to the problems of intercultural communication and the use of multimedia technologies in team activities, in particular when learning a foreign language. As a conclusion, we suggest that the organization of team work on virtual communication platforms is crucial in the context of learning. Virtual communication platforms have contributed to the fact that the educational process has become more accessible to everyone. Team activity has become an important tool for organizing educational processes in the modern educational and informational environment.